Gut gegen Weihnachtsstimmung – Kulturwissenschaftliche Lesarten eines Festes - Ahner, Helen (DMW - Deutsche Medizinische Wochenschrift, 2019)
Christmas is a celebration with a strong social radiance. It is a vehicle for political positions and debates and thus shows itself to be a controversial cosmos of significance. A cosmos with history that is not as old as is often claimed – the origin of the festival as we know it today lies in the 19th century. Since then, Christmas has developed into a global festival in which many different people take part. But Christmas is not only unifying, it is also exclusive and creates cultural differences. The aim of the text is to look at the festival in its historical genesis and to critically illuminate Christmas as an ambivalent social phenomenon.
Keywords: Weihnachten; Vielfalt; Gesellschaft; Kultur